Unity of purpose can help Nigeria and Africa to achieve SDG2 goal - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
Ebonyi State Deputy governor,Dr Kelechi Igwe, giving his remarks at the Launch of Nigeria strategic plan and roadmap to achieve zero hunger by 2030. The plan tagged: “Synthesis Report of the Nigeria Zero Hunger Strategic Review” articulates what Nigeria needs to do to achieve Sustainable Development Goal 2 (SDG2)—one of the recently adopted global goals that seeks to “end hunger, achieve food security and improved nutrition, and promote sustainable agriculture” by 2030.